New association between the mite Erythraeus sp. (Acari: Prostigmata: Parasitengona) and the psyllid Russelliana adunca (Hemiptera: Psylloidea) - Baliotte, Carla (2021)
The association between the ectoparasitic mite, Erythraeus Latreille (Acari: Prostigmata: Parasitengona) and the psyllid Russelliana adunca Burckhardt (Hemiptera: Psylloidea) is reported for the first time. Larval erythraeid mites are not common on psyllids, therefore this first report adds a new host association and widens the distribution of the mite in South America.